Effects of Eimeria acervulina infection on the luminal and mucosal microbiota of the duodenum and jejunum in broiler chickens - Campos, Philip M.; Miska, Katarzyna B.; Jenkins, Mark C.; Yan, Xianghe; Proszkowiec-Weglarz, Monika (Frontiers in Microbiology, 2023)
The intestinal disease coccidiosis, caused by Eimeria parasites, impacts nutrient absorption in broiler chickens, leading to weight gain depression and major losses in the poultry industry. To develop alternatives to antibiotics for treating infected chickens, the gut microbiota has been researched because of its association with health factors such as nutrient exchange, immune system modulation, digestive system physiology, and pathogen exclusion. The aim of this study was to determine the effect of Eimeria acervulina infection on the luminal and mucosal microbiota of both the duodenum (DuoL and DuoM) and jejunum (JejL and JejM) at multiple time points (days 3, 5, 7, 10, and 14) post-infection. 16S rRNA amplicon sequencing was utilized to characterize the microbiota and analyze differences in alpha and beta diversity between infected (IF) and control (C) birds at each time point. Alpha diversity differed between IF and C birds in DuoM and JejM microbiota. Combined with beta diversity results, DuoM microbiota appeared to be affected by infection in the longer-term, while JejM microbiota were affected in the shorter-term. Relative abundances of bacterial taxa known for short-chain fatty acid (SCFA) production, such as Lachnospiraceae, Subdoligranulum, and Peptostreptococcaceae, tended to be lower in IF birds for all four microbiota. Moreover, predicted functional abundances showed MetaCyc pathways related to SCFA production, especially butyrate, may be influenced by these differences in bacterial relative abundance. Our findings expand understanding of how Eimeria infection affects luminal and mucosal microbiota in the duodenum and jejunum, and further research on metagenomic function may provide insights on the degree of influence duodenal and jejunal bacteria have on chicken health.